Influence of biofertilizer on growth improvement of aerobic rice genotypes - Taketsaba, A. I.; Juraimi, A. S.; Yusop, M. R.; Othman, R.; Singh, A. (2018)
Biofertilizers have emerged as a potential environment friendly inputs that are supplemented for proper plant growth.Two field experiments were conductedat University Putra Malaysia (UPM), Selangor, Malaysia during 1st season (Mayto September 2015) and 2nd season (September to December 2015)to evaluate the performance of aerobic rice genotypes under different combinations of bioandchemical fertilizer. The experiment consisted of five (5)biofertilizer combinations (chemical fertilizer recommended rate (CFRR) (150 N; 60 P2O5;60 K2O kg ha-1) 100%,biofertilizer 1 ton+ 75%CFRR,biofertilizer 2 tons + 50%CFRR,biofertilizer 3tons+ 25%CFRR,and biofertilizer 4 tons)and three aerobic rice genotypes (MRIA1, MR219-4 and MR219-9)laid out in a split-plot in randomized complete block design(RCBD) with 3 replicates.Results revealed that application of biofertilizer 1 ton + 75%CFRR produced the highest plant height (102.65 cm) and an umberof tillers (20.38) in the 2nd season, the highest grain yield (4.30 t ha-1) than theother biofertilizer treatments in the 1st season. MR219-4 produced the highest number of tillers, leaf area and leaf photosynthesis rate in both seasons,grain yield (5.02 t ha-1) in 1st season while MR219-9 produced the highestcropbiomass (52.76 g hill-1) and crop growth rate (8.00 g hill-1week-1) at 12 WAS,grain yield (3.86 tha-1) than the other genotypes in the 2nd season.The trend in these results indicated that biofertilizer tend to be more effective with limited chemical fertilizer in the 1st season of low rainfall.These results concluded that 1 ton biofertilizer + 75% CFRR andMR219-4enhancesrice growth and grain yield in aerobic condition.